IMPLIKASI KEBIJAKAN PENGANGGARAN PROGRAM E-KTP DI KECAMATAN TAMBUSAI DAN TAMBUSAI UTARA KABUPATEN ROKAN HULU TAHUN 2011-2012 - Rezeki Ridho; Erman Muhtar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Sustenance REZEKI RIDHO (0901133225) , " Policy Implications of e - ID card Budgeting in District Tambusai and North Tambusai Rokan Hulu in 2011-2012". This research is motivated by the existence of programs designed by the Central Government through the Minister of the Interior of the national ID card in order to make the data population in Indonesia is not a double . Related to this would be the main implementers of Local Government . Similarly circuitry Rokan Hulu . The program began in 2011, but can only be effectively implemented in mid-2012 . It is the target of becoming the fastest districts in the implementation of the national e - ID card . It turned out that the plan is achieved , but it turned out to be the result of the implementation of e-ID in Rokan Hulu itself varies . Of the 16 districts are the two districts with the lowest implementation , namely Kacamatan Tambusai and North Tambusai . Allegedly this is caused by the implementation of the policy system operasipnal incorrect e - ID card , which is set equal anggaranyang for all districts , whereas these two densely populated districts would require more budget too much . In this regard certainly drawn up plans to be realized . However , what has been planned that the results have not been able to reach the target . Where these two districts until today have to process people who have not made the recording , resulting in the delivery of data center becomes slow.The results of this study indicate that : 1 ) the implementation of e-ID in the District of North Tambusai Tambusai and relatively slow . 2 ) budgeting system which does not consider the real conditions in the field to be one of the obstacles that have implications for other aspects . 3 ) the lack of public awareness of the importance of the e - ID card program . 4 ) the availability of facilities such as electrical and instrument recording is limited to one of the barriers to the implementation of e - ID card recording in District Tambusai and especially North Tambusai. Keyword : policy , budget implications , Performance Monitoring , and Corection Action.